Evaluating career planning preparedness in Bengkulu vocational high school students - Nandang Rusmana; Juntika Nurihsan; J Juwanto (KONSELOR, 2023)
Career planning is an important aspect in the career development process because it will have an impact on the student's future. It is hoped that the existence of Vocational High Schools (SMK) will be a step for the government and schools in providing students who are ready to work. Vocational School is a vocational education institution that has an important role in developing the quality of graduates who are ready to work and respond to the needs and developments of the times. The high unemployment rate in the 15–19-year age group nationally emphasizes that junior high school and high school/vocational school levels are important age phases in formulating future careers. The aim of this research is to determine students' readiness in career planning at Bengkulu Vocational School. The method used is survey research. The instrument developed was an inventory which, using data collection techniques, was distributed to 124 vocational school students via Google Form, which was then analyzed using Rasch modeling. Based on the data obtained, overall self-readiness in career planning for vocational school students is in the high category at 19%, in the medium category at 67%, and in the low category at 14%. Thus, it can be concluded that vocational school students in Bengkulu have not prepared themselves optimally in good career planning. Based on the findings, appropriate management of student career development in schools is needed. So it will have an impact on students' career maturity. A student's career is not only limited to a choice of job and work, but how students can manage and formulate career plans well so as to achieve career success in the future.